Hambatan Guru BK Dalam Mengembangkan Rencana Pemberian Layanan BK (RPLBK) Berdiferensiasi - Pithriani, Pithriani; Apriatama, Dony; Br Ginting, Herda Fitri (Universitas Palangka Raya, 2024)
BK teachers are expected to be able to compile and develop RPLBK according to the characteristics and needs of students (differentiated) at school. This study aims to identify the obstacles faced by counseling teachers in developing differentiated EAPs. The method used was descriptive qualitative with data collection techniques in the form of questionnaires and interviews. A total of 31 counseling teachers from 11 junior high schools in Palangka Raya City filled out the questionnaire, and interviews were conducted with the head of PD-ABKIN Central Kalimantan and the head of MGBK Central Kalimantan. The results showed that most counseling teachers did not understand and implement differentiated RPLBK. This is due to teachers' low skills in using technology, lack of support from stakeholders, and the absence of clear regulations regarding the use of differentiated RPLBK. In addition, the lack of appreciation and financial support is also an inhibiting factor. Therefore, stakeholders need to make regulations that encourage the improvement of counseling teachers' ability to design differentiated RPLBK, and provide intensive training to improve technology skills and understanding in the preparation of differentiated RPLBK.